Hubungan Kecenderungan Adiksi Game Online dengan Kecerdasan Emosional Siswa SD Negeri X - Faizah Salma; Laelatus Syifa Sari Agustina (UNS Press, 2025)
The number of students using online games has increased due to easy access to the internet and technology. This study aims to analyze the effect of online game addiction on the emotional intelligence of elementary school students. The population in this study were 96 students of SD Negeri X from grades 1 to 6. While the sample used was 82 students with the criteria of having or currently playing online games. A questionnaire with a Likert scale was used to collect student assessments regarding the use of online games and the level of students' emotional intelligence. Validity and reliability tests are used to prove the validity of the data collected. Normality test, linearity and hypothesis testing are used as data analysis techniques. The research results show that all data is valid and reliable. Linear test showed p=0.615 so there is a relationship between online game addiction and emotional intelligence. The results of the hypothesis test also prove that there is an influence of online game addiction on the emotional intelligence of elementary school students with a significance value of 0.000 and a correlation coefficient of 0.489.